The Effect of The Use of Augmented Reality Learning Media on Students' Learning Interest in Mathematics Learning in Grade V at State Elementary School 1 Darma - Aditiya, Tesa; Saeful Anwar, Agus (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to obtain information about the effect of the use of Augmented Reality learning media on students' interest in learning mathematics in grade V in Elementary Schools, so that empirical information is obtained. A quantitative approach with Quasi Experimental Design with Nonequivalent Control Group Design was chosen as the method in this study. This method is used with an initial test (pretest) to determine the initial conditions, after which a final test (posttest) is given. After testing the hypothesis, the Paired Sample T Test obtained a sig. 0.001 <0.05. These results indicate that there is a fairly good influence on the application of Augemneted Reality learning media on students' interest in learning, thus indicating that Ha can be accepted. Meanwhile, to compare the differences in the results of students' interest in learning, the Independent Sample T Test obtained a sig. 0.015 <0.05. This shows that there is a difference between the application of Augmented Reality learning media and the application of conventional learning.